The Degrees of Hearing Loss and Hearing Handicap Inventory for the Elderly-Screening - muyassaroh - -; dwi - marliyawati; joyo - wardoyo (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: Hearing loss causing communication problems and affect the quality of life. The Hearing Handicap Inventory for the Elderly-Screening (HHIE-S) can be used as a screening tool for assessing the impact of hearing loss. Objective: To determine the correlation between the degree of hearing loss and The Hearing Handicap Inventory for the Elderly-Screening (HHIE-S). Method: This was an analytic observational study with a cross-sectional design on 86 elderly who met the inclusion and exclusion criteria. Hearing loss was determined by audiometric examination. HHIE-S was used to assess the impact of hearing loss. The ethical approval was obtained from the Research Ethics Commission of Dr Kariadi Central Hospital, Semarang. Data were analyzed using the Spearman's Correlation test. P-value of <0.05 was considered significant. Result: There was no significant correlation between age and sex with HHIE-S (p = 0.115; r = 0.302). There was a significant correlation between the degrees of hearing loss and HHIE-S (p = 0.000, r = 0.379). Conclusion: The degrees of hearing loss was correlated to HHIE-S.